MODEL PENCEGAHAN FRAUD PADA ALOKASI DANA DESA DI DESA GABUS KABUPATEN PATI - Fuad, Khoirul; Mustaqin, Khoyrul (AKUNTANSI DEWANTARA, 2024)
The amount of village fund allocation, considered quite large, is a big responsibility for village officials to manage the village funds. In a situation like this, it is possible to create the potential for the village government to make deviations. These deviations can occur individually, even the riskiest, namely in groups. This happens because of 3 conditions commonly referred to as the "Fraud Triangle" by Cressey in 1953, namely the opportunity (opportunity), the pressure (pressure), and because of the attitude or character (rationalization), so this study aims to determine the competency variables of the village apparatus, internal control systems and morality have a positive effect or not on the prevention of fraud (fraud). The sampling technique used in this study is non-probability sampling; the non-probability sampling technique is the convenience sampling method, namely the research sampling technique based on the availability of elements and the ease of obtaining them. The sample was selected because the presence of the person or unit was in the right place and at the right time so that it was easy to find and directly involved in the management of village funds. The results of this study indicate that the competence of the village apparatus has a significant negative effect on fraud prevention, besides that the internal control system has a significant positive effect on fraud prevention. In contrast, morality has a positive but not significant impact on fraud prevention.